Smart numafit songs as a mathematics in context-based learning media for elementary numeracy education - Ayu Fitri; Turmudi; Jupri, Al; Rakhmat Riyadi, Arie; Safarandes Asmara, Andes; Nur DS, Yulistina (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to examine the effectiveness of Smart Numafit Songs based on Mathematics in Context (MiC) as a numeracy learning medium for improving fifth-grade elementary students’ numeracy skills.Method: This study employed a quantitative approach using a one-group pretest–posttest design involving 43 fifth-grade students selected through purposive sampling. The intervention utilized Smart Numafit Songs generated with Suno AI and contextual cartoon videos developed using OpenArt AI. The numeracy test measured four domains: Basic Numeracy Skills, Problem and Formulation, Communication and Interpretation, and Application in Context. Data were analyzed using descriptive statistics, paired-samples t-tests, effect size analysis, and N-Gain with SPSS version 31.Findings: Students’ mean numeracy score increased from 45.95 in the pretest to 86.23 in the posttest. The paired-samples t-test revealed a statistically significant difference between pretest and posttest scores (p < .001). The intervention produced a very large effect size (Cohen’s d = 4.711), while the N-Gain score reached 0.71, indicating a high level of improvement in students’ numeracy skills.Significance: The findings demonstrate the potential of integrating Mathematics in Context, AI-generated songs, and contextual visual media to support numeracy learning in elementary education. Smart Numafit Songs provide an innovative, contextual, and multimodal learning medium that can enhance elementary students’ numeracy development.